Pandemic Opens Opportunities to Solve Pathology Manpower Challenges Worldwide - Hassell, Lewis A.; Afzal, Anoshia (Frontiers in Communication, 2021)
Conventional processes of pathology education have been disrupted by the pandemic of 2020, forcing a re-evaluation of the means of teacher-learner interactions. Digital and remote teaching methods have become the standard, spearheaded by several national and international organizations and enforced by a need to social distance during a pandemic. At the same time, the public health predictions regarding the impact of non-communicable diseases on the developing world, and the resultant increased demand for pathology services to help cope with that tidal wave of disease, presents a challenge to a declining population of pathologists in North America. However, the shift in teaching methods has produced a wealth of on-line training resources. This offers for the first time a leveraging effect on the teaching value of pathology expertise, largely concentrated in the developed world, and an opportunity to both enhance and equitize training internationally, potentially sufficient to meet the rising wave of non-communicable diseases ahead in the next 20 years. We propose four next steps to take advantage of the current opportunity to meet this challenge: Curate and organize digital training materials; Invest in the digital pathology infrastructure for education and clinical care; Expand student exposure to pathology thru virtual or in person electives; Develop further competency-based rather than time-based certification and board eligibility.